Initial Linkage and Subsequent Retention in HIV Care for a Newly Diagnosed HIV-Infected Cohort in Denver, Colorado. (November 2013) - Gardner, Edward M.; Daniloff, Elaine; Thrun, Mark W.; Reirden, Daniel H.; Davidson, Arthur J.; Johnson, Steven C.; Wilmoth, Ralph; Connick, Elizabeth; Burman, William J.
This is a retrospective cohort study of 352 newly diagnosed HIV-infected individuals in Denver, from 2005 to 2007. Utilizing data from 3 health care systems, 2 clinical trials units, and statewide Colorado HIV laboratory reporting databases, we tracked initial linkage to HIV care, retention in care, loss to follow-up, and transitions between HIV care providers. After more than 2.6 years of follow-up, 256 (73%) individuals linked to HIV care within 180 days. Of the 301 individuals who eventually linked to care, 168 (56%) had at least one 180-day gap in care, while 49 (16%) had a 360-day gap. Transitions in care were common, with 131 (37%) individuals accessing care from 2 different providers and 15% having evidence of living outside of Colorado. In this newly diagnosed HIV-infected cohort, linkage to care was slow and long-term retention in care was poor. Transitions between HIV care providers were common and may impair engagement in care over time. Out-of-state migration was frequent and may cause an underestimation of engagement in care.